Socialization of Table Tennis Refereeing to KKGO Duren Sawit, East Jakarta - Asri, Novri; Wenly, Ayu Purnama (STKIP Singkawang, 2025)
Community Service Activities entitled Socialization of Table Tennis Refereeing to KKGO Duren Sawit, East Jakarta, aims to provide socialization regarding table tennis refereeing to members of KKGO Duren Sawit, East Jakarta. This socialization was carried out to improve participants' understanding and skills regarding the role of a referee in a table tennis match, as well as to provide an in-depth understanding of the applicable regulations in the sport. This activity includes the presentation of material regarding the duties of a referee, match regulations, and simulation of referee practice in a table tennis match. The results of this activity showed that participants experienced an increase in knowledge regarding table tennis refereeing, as well as acquired basic skills in decision-making as a referee. The response of participants to this activity was very positive, with many showing interest in becoming referees in local tournaments. However, to optimize the quality of refereeing at the local level, further training, more practice opportunities, and collaboration with related organizations or federations are needed. This socialization is expected to contribute to the development of the quality of refereeing and the organization of more professional table tennis tournaments in East Jakarta.Sosialisasi Perwasitan Tenis Meja kepada KKGO Duren Sawit, Jakarta TimurABSTRAKKegiatan Pengabdian kepada Masyarakat dengan judul Sosialisasi Perwasitan Tenis Meja kepada KKGO Duren Sawit, Jakarta Timur, bertujuan untuk memberikan sosialisasi mengenai perwasitan tenis meja kepada anggota KKGO Duren Sawit, Jakarta Timur. Sosialisasi ini dilaksanakan untuk meningkatkan pemahaman dan keterampilan peserta terkait peran seorang wasit dalam pertandingan tenis meja, serta memberikan pemahaman mendalam mengenai peraturan yang berlaku dalam olahraga tersebut. Kegiatan ini meliputi pemaparan materi mengenai tugas wasit, peraturan pertandingan, serta simulasi praktik wasit dalam pertandingan tenis meja. Hasil dari kegiatan ini menunjukkan bahwa peserta mengalami peningkatan pengetahuan mengenai perwasitan tenis meja, serta memperoleh keterampilan dasar dalam pengambilan keputusan sebagai wasit. Tanggapan peserta terhadap kegiatan ini sangat positif, dengan banyak yang menunjukkan minat untuk menjadi wasit dalam turnamen lokal. Meskipun demikian, untuk mengoptimalkan kualitas perwasitan di tingkat lokal, dibutuhkan pelatihan lanjutan, kesempatan praktik lebih banyak, dan kolaborasi dengan organisasi atau federasi terkait. Sosialisasi ini diharapkan dapat memberikan kontribusi terhadap pengembangan kualitas perwasitan dan penyelenggaraan turnamen tenis meja yang lebih profesional di Jakarta Timur.Kata Kunci :Sosialisasi; Wasit; Tenis Meja